Pengembangan Media Pembelajaran Puzzle Hak dan Kewajiban untuk Meningkatkan Kerja Sama Peserta Didik Kelas III Sekolah Dasar - Sari, Fathmatya Ryza Kirana; Utomo, Arief Cahyo (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2024)
This study aims to develop learning media based on rights and obligations puzzles to determine the validity, feasibility, practicality, and effectiveness of improving students' cooperation skills. This study is a type of development research or Research and Development (R&D) with the Four D (4-D) method of defining, designing, developing, and disseminating. The data analysis techniques used are 1) qualitative descriptive analysis carried out through data grouping in the form of suggestions on the results of validation sheets by experts and product trials and 2) quantitative descriptive analysis for data processing in the form of percentages. Data collection techniques using interviews, validation sheets, observation sheets, and response questionnaire sheets. The results obtained are: 1) validation by media experts produced a percentage of 85% and 97.5%, which can be interpreted that the lesson media is very feasible to use; 2) validation by material experts produced a percentage of 95% which can be interpreted that the material in the media is appropriate and very feasible to present, 3) the student response questionnaire produced a percentage of 95.21%, and the educator response questionnaire produced a percentage of 95.83% which can be interpreted that the puzzle learning media is very practical to use, 4) the results of observations of students' cooperation skills obtained the results of the difference before use and after use of 31.68% so that it can be interpreted that the Rights and Obligations puzzle learning media can improve students' cooperation skills.